The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.5336/medsci.2009-13696
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age and its Relationship with Elbow Width, Wrist Width and Forearm Length

Abstract: A AB BS S T TR RA AC CT T O Ob b j je ec c t ti i v ve e: : Fe tal de ve lop ment has been a sub ject of gre at in te rest from ear li est ti mes to the pre sent day and can to day ea sily be analy zed using ul tra so und (US) and si mi lar de vi ces. The lengths or di a me ters of va ri o us fe tal struc tu res are me a su red, and in tra u te ri ne age and de ve lopment can thus be mo ni to red. Our study in ves ti ga tes the va lu e of a se ri es of lengths me a su red in the up per ex tre mity in the mo ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…On the other hand, as the result of the study conducted by Uluutku et al on 21 fetuses involving 17-35.8 gestational weeks, the total width of the right wrist is said to be 15.25 mm, whereas the total width of the left wrist is said to be 15.27 mm; on the other hand, the total width of the right elbow is stated to be 18.85 mm, while the total width of the left elbow is stated to be 18.87 mm. Separately, just as the result seen in our study, it is reported in each of these three studies that there is no difference between sexs, nor between right-left parts of the forearm (Malas et al, 2000;Uluutku et al). There are differences between the results of our study and those of the other studies in terms of the mean values pertaining to the parametric measurements.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…On the other hand, as the result of the study conducted by Uluutku et al on 21 fetuses involving 17-35.8 gestational weeks, the total width of the right wrist is said to be 15.25 mm, whereas the total width of the left wrist is said to be 15.27 mm; on the other hand, the total width of the right elbow is stated to be 18.85 mm, while the total width of the left elbow is stated to be 18.87 mm. Separately, just as the result seen in our study, it is reported in each of these three studies that there is no difference between sexs, nor between right-left parts of the forearm (Malas et al, 2000;Uluutku et al). There are differences between the results of our study and those of the other studies in terms of the mean values pertaining to the parametric measurements.…”
Section: Discussionsupporting
confidence: 68%
“…When we reviewed the former studies as regards fetal forearm development, we did not come across any study that investigated the development of the forearm during the fetal period through radiological methods. The studies in this matter were conducted on dead fetuses and were concerned with the morphometric measurements of upper and lower limbs on dead fetuses (Malas et al, 2000;Malas et al, 2005;Uluutku et al). Separately, they involved ultrasonographic studies regarding the measurements of limb that were performed during the fetal period (Huang et al; Chen et al; Song & Wang).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations